BCL2 Expression in the Brains of Diabetic Rats Treated with Ginger - Mohammad Mohsen Taghavi; Seyed Hassan Eftekhar-Vaghefi; Zahra Taghipour; Ahmad Shabanizadeh; Abdolreza Babaee; Ilia Najmadini; Akram Molahosseini (Iranian Journal of Diabetes and Obesity)
Objective: Diabetes is one of the most common high-risk diseases which causes many side effects in most body systems such as the nervous system. The medicinal plants, has been suggested to reduce the side effects of this diseases. In this experimental study, we examined the effect of ginger on BCL2 gene expression in the hippocampus of diabetic rats. Materials and Methods: In this experimental study, we used 60 Wistar rats (200gr). We separated the rats into one healthy group and four groups of diabetics which after seven days of diabetes induction via Streptozotocin (60 mg/kg), received different mixture of insulin and ginger for 6 weeks. 24 hours after the last injection, brains of rats were removed and the hippocampus region was studied histologically and the BCL2 gene expression examined by Real-time PCR. Results: According to the results, the blood glucose level in the ginger treated group (183.17) decreased significantly compared to the diabetic control group (232.5) (P˂ 0.01). In the expression of BCL2 gene, there was not any significant difference among the groups. In the histological examination of the hippocampus CA1 region, the ginger-insulin treated group had less pyknotic neurons than the diabetic control group.